Systematic Literature Review: Pengaruh Product Affiliator dalam Meningkatkan Penjualan Produk Fashion di Marketplace Shopee - Ketut Witara (Universitas 45 Surabaya, 2024)
This study aims to analyze the impact of product affiliation on increasing fashion product sales on the Shopee marketplace using a Systematic Literature Review approach. This research approach involves collecting, analyzing, and synthesizing information from various relevant and valid literature sources. Product affiliation, as a marketing technique involving collaboration with third parties to market products, has become an increasingly popular method among online sellers. The results of the literature review indicate that the implementation of product affiliation has a significant positive impact on increasing fashion product sales on Shopee. This impact is particularly evident in the increased visibility of products, more focused market targeting, and increased consumer trust in products marketed by reliable affiliates. In addition, this approach has also proven effective in increasing engagement and interaction between consumers and brands, which ultimately contributes to increased sales conversion. However, this study also found several challenges that must be addressed, such as selecting the right affiliates, assessing the effectiveness of affiliate campaigns, and managing relationships with existing affiliates. By understanding these factors, sellers on Shopee can optimize the benefits of using affiliate programs and increase their fashion product sales more effectively. This study is expected to make a significant contribution to digital marketing and offer useful guidance for online sellers in implementing product affiliation strategies to achieve their sales targets. Further research is recommended to investigate the use of quantitative methods in assessing the long-term effects of affiliate programs on sales across various product categories.